Haematopoietic Stem Cell Transplantation: A Single Center Experience of Four Years in Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: Haematopoietic stem cell transplantation (HSCT) is the standard consolidation therapy for a variety of malignant and non-malignant diseases in children and adults. Our experience of HSCT in 26 patients with various indications is shared in this article.Materials and methods: This was a retrospective analysis of first 26 patients who had undergone autologous and allogeneic transplant at our center, with M:F=2.7:1. The mean age for autologous transplant was 45 years (range 23-57 years). The median follow-up period was 23 months 25 days (range 3to 47 months).The data was obtained carefully from medical records of the BMT center. Indications for autologous HSCT were Multiple Myeloma (12 patients), Non- Hodgkin’s lymphoma (7 patients), Hodgkin’s lymphoma (4 patients). Allogeneic HSCT were for Acute Myeloid Leukaemia (3 patients).Results: The mean time for WBC engraftment was 12 days (range: 9-19 days) and for platelet engraftment was 16 days (range: 11-35 days) in our autologous transplant cases and for allogeneic transplant mean time for WBC engraftment was12 days (range: 11-15 days) and for platelet engraftment was 14 days (range: 12-17 days). Irradiated blood components were given in the pre, peri and post-transplant period to maintain Hb>8 gm/dl and platelet count >20X109/L. Mean single-donor platelet requirement was 4 units (range 1-7), and mean packed red cell requirement was 1.5 units (range 1-6). The post-transplant complications encountered were mucositis, infections and diarrhoea. Oral mucositis was the most common complications. Twenty three (88.46 %) out of our 26 HSCT patients had developed mucositis , among them grade 1 in 5 patients, grade 2 in 11 patients, and grade 3 in 7 patients. There were 21(80.76%) cases of febrile neutropenia. Out of 26 patients 13 (50.0%) bacterial infection were documented with culture positivity. One (3.84%) case of viral infection was documented. Major bacterial infections were culture positive with Pseudomonas, Escherichia coli and Klebsiella followed by other species like acinatobacter, burkholderia and coagulase negative staphylococcus. One case of Cytomegalovirus was noted with significant viral copies that required Ganciclovir. Average duration of hospital stay after autologous HSCT was 23 days (range of 14-54 days) and allogeneic HSCT was 35 days (range of 30-57 days). 19 out of our 23 autologous transplant patients were in complete remission and all 03 cases of allogeneic HSCT were in remission.Conclusion: We believe our center has made a remarkable progress within short period of time to develop both autologous and allogeneic HSCT and is comparable with nationally and internationally renowned HSCT centers in terms of standard, quality and safety of care, and the ultimate outcomes.J Bangladesh Coll Phys Surg 2022; 40: 146-152